The Effect Of Incomeintention On Financial Well Being: Household Behavior As A Mediating Variable Study on Fisherman Families in Bantul Regency, Yogyakarta - Bangun Putra Prasetya; Nany Noor Kurniyati (University of Science and Computer Technology, 2023)
Optimizing the potential development of the south side of Yogyakarta can be used as one of the ways in poverty alleviation at the level of life of Yogyakarta fishermen. The welfare of traditional fishermen is influenced by a number of factors, namely limited quality of human resources, limited business capital capacity and fishing technology information. Regarding income levels, community welfare can be achieved by one of them by achieving Financial Well Being. This study aims to determine the effect of the income level of fishermen in Bantul Regency, Yogyakarta in achieving Financial Well Being by paying attention to household behavior as a mediation variable. The population in this study is fishermen along the coast of Bantul Regency under the guidance of related agencies. The sample in this study was 99 fishermen. Hypothesis testing using Smart PLS. The results of research conducted on fishing families in Bantul Regency, Special Region of Yogyakarta stated that Incomeintention has an effect on Financial Well Being. In addition, if a person's Incomeintention is balanced with the ability to control household behavior in controlling finances and saving, it will have a good impact on Financial Well Being